Deskripsi Pemahaman Cyberbullying di Media Sosial pada Mahasiswa - Mutma, Fasya Syifa (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2020)
The development of internet technology and social media is accelerating the process of disseminating information. This certainly makes it easier for human life. But the rapid pace of information technology can have a negative impact if it is not put to good use. At the moment there is a rampant cyberbullying case, which is the bullying that occurs through cyber media, in this case, social media. Cyberbullying has a bad impact on victims such as causing depression, so that the worst is causing death due to suicide. Cyberbullying is often a big problem both in the national and global order. There have been many cases that have occurred, the most numerous being teenagers who committed suicide due to experiencing cyberbully. Because of this, researchers are interested in researching more about cyberbullying. In this study, researchers wanted to find out how much the level of understanding of adolescents towards cyberbullying behavior. This study uses a positivistic paradigm with data collection methods, namely questionnaire survey. The sample of this study were students from one of the universities in South Tangerang.